Improved Morphine-Loaded Hydrogels for Wound-Related Pain Relief - Dinis Mateus; Joana Marto; Patrícia Trindade; Humberto Gonçalves; Ana Salgado; Paula Machado; António Melo-Gouveia; Helena M. Ribeiro; António J. Almeida (MDPI AG, 2019)
The use of morphine applied topically to painful wounds has potential advantages, such as dose reduction, fewer side effects and compound formulations, have been proposed for this purpose. Given the potential high impact of drug product quality on a patient’s health, the aim of the present study was to develop two stable sterile hydrogels containing morphine hydrochloride, intended for topical application on painful wounds. Two carboxymethylcellulose sodium-based hydrogels were prepared containing 0.125% w/w (F1-MH semi-solid formulation) and 1.0% w/w (F2-MH fluid formulation) morphine hydrochloride (MH), respectively. Studies included a risk assessment approach for definition of the quality target product profile (QTPP) and assessment of critical quality attributes (CQA) of the hydrogels to support product quality and safety. Safe, odourless, yellowish, translucent and homogeneous gels were obtained, with suitable microbiological and pharmaceutical characteristics. The active substance concentration was adapted according to the characteristics of the dose-metering device. Release profiles were investigated using Franz diffusion cells, and characterised by different kinetic models. Increasing gel viscosity prolonged drug release, with rates of 17.9 ± 2.2 μg·cm−2·h−1 (F1-MH) and 258.0 ± 30.4 μg·cm−2·h−1 (F2-MH), allowing for the reduction of the number of applications and improving patient compliance. The gels proved to be stable for up to 60 days at room temperature. The semi-solid and fluid MH-containing hydrogel formulations are safe, stable and suitable for use in hospital settings, which is rather important for wound-related pain management in cancer palliative care or burn patients.